Masyarakat Bugis di Kota Tua Ampenan Mataram - Ilmiawan, Ilmiawan; Sarah, Fidlia Mae (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
The old town of Ampenan is a strategic area. This can be seen from the point of view of socio-cultural interests where this area has become a cultural heritage of Mataram City based on the Building and Environmental Planning (RTBL). And this is in accordance with the Regional Long and Medium Term Development Plan (RPJMD) of Mataram City, namely in 2016-2021 regarding Ampenan Old Town which has historical values, preservation of local customs and culture which is one of the identities of the local community's local wisdom. This research aims to explore the history and social dynamics of the Bugis community who settled in the Old Town of Ampenan Mataram. The approach used in this research is through a socio-historical study approach, meaning that data collected through interviews, observations, and literature studies to produce an in-depth understanding of the adaptation and contribution of the Bugis community to city life. Based on the results of observations and interviews that have been conducted, it can be formulated the problem studied, namely exploring the development of the Bugis community in the context of urban history, social transformation, and interaction with the surrounding community.